Complications in aesthetic medicine resulting from procedures that use fractional lasers in skin regeneration treatments - Beutler, Katarzyna; Rzepczyk, Szymon; Bijata, Bartosz; Lewandowski, Jędrzej; Świderski, Paweł (Aesthetic Medicine, 2024)
Fractional lasers are used in aesthetic medicine for skin resurfacing, the number of treatments that employ them is constantly increasing. They represent a safer alternative to the previously dominant full ablative and non-ablative lasers, due to the smaller area of skin exposed to the laser. Despite improved technology and increased safety of laser treatments, as well as their shortened recovery time, complications still occur. The most common ones include erythema or swelling, however serious and long-term complications also occur. Considering the risk of complications and their severity, the person performing the procedure should be well trained, use appropriate equipment with correctly selected parameters and follow the principles of antisepsis. The number of lawsuits against people performing laser treatments is growing significantly, as patients are suing for compensation. Due to the fact that the continuity of the skin is not broken during the procedure, in many countries there are no precise legal regulations regarding the principles of laser treatments, which significantly complicates the pursuit of such claims.